Auto-identification and ubiquitous computing applications RFID and smart technologies for information convergence - Symonds, Judith, 1972-; Ayoade, John, 1970-; Parry, Dave, 1963 July 11-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book reports on practical problems and underlying theory related to the use of primary RFID technologies"--Provided by publisher.
Section 5. Selected Readings -- Chapter 12. An Agent-Based Library Management System Using RFID Technology / Maryam Purvis, Toktam Ebadi, Bastin Tony Roy Savarimuthu -- Chapter 13. Semantic-Based Bluetooth-RFID Interaction for Advanced Resource Discovery in Pervasive Contexts / Tommaso Di Noia, Eugenio Di Sciascio, Francesco Maria Donini, Michele Ruta, Floriano Scioscia, Eufemia Tinelli -- Chapter 14. Facing the Challenges of RFID Data Management / Indranil Bose, Chun Wai Lam -- Chapter 15. A Mobile Computing Framework for Passive RFID Detection System in Health Care / Masoud Mohammadian, Ric Jentzsch-- Chapter 16. Intelligent Agents Framework for RFID Hospitals / Masoud Mohammadian, Ric Jentzsch -- Chapter 17. Radio Frequency Identification (RFID) Technology / David C. Wyld -- Compilation of References -- About the Contributors -- Index.
Includes bibliographical references (p. 294-318) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 25, 2010).
Keywords: Radio frequency identification systems -- Industrial applications; Data modelling; Fixed-mobile convergence; Online tracking; Radio frequency identification; RFID and assisted living for the elderly; RFID for identification of stolen/lost items; RFID in emergency management; RFID in hospitals; Traceability management; Wireless indoor user positioning; Electronic books